Cardiac Stab Wound in Remote Area: A Case Report - Sukanto, Wega; Tamburian, Christha Z.; Aruperes, Marturia I. (Universitas Sam Ratulangi, 2025)
Abstract: Penetrating cardiac injuries are life-threatening emergencies requiring immediate surgical intervention. We presented a case of cardiac stab wound leading to cardiac tamponade and rupture of the pulmonary artery and right ventricle who survived long enough to undergo emergency procedure. A 25-year-old male was stabbed in the left chest approximately nine hours before admission. He experienced chest pain and dyspnea but remained conscious. After initially treated at a local hospital, he was later referred to a tertiary facility. On assessment, he was tachycardic, tachypneic, and had distant heart sounds. Laboratory findings revealed leukocytosis, thrombocytosis, hyperglycemia, metabolic acidosis, lactic acidosis, and anemia. Chest radiograph showed a bottle-shaped heart, passive atelectasis, and a rightward shift of the thoracic vertebrae. The initial suspicion was cardiac tamponade due to myocardial rupture. Sternotomy revealed a pericardial hematoma (150 mL), a right ventricular tear extending to the pulmonary artery, and pneumothorax. Surgical repair was performed with drainage placement. After intervention, echocardiograph examination showed no myocardial damage or infarction, a dysfunction in diastolic which showed an impaired in relaxation of the left ventricle which is a temporary consequence of trauma, pericardial effusion or surgical intervention. In conclusion, this case underscores necessity of early surgical intervention even if this patient succeeded surviving for long hours before surgery. While this patient showed promising recovery, close postoperative monitoring remains crucial to detect functional changes and prevent complications. Keywords: emergency sternotomy; vulnus ictum; chest trauma; sharp cardiac injury; repair of artery pulmonary; rupture of right ventricle